In silico based screening of WRKY genes for identifying functional genes regulated by WRKY under salt stress. (December 2019) - Hassan, Sameer; Lethin, Johanna; Blomberg, Rasmus; Mousavi, Hesam; Aronsson, Henrik
Graphical abstract: Highlights: The recently published wheat genome contains 297 WRKY transcription factor genes and 355 transcript variants. We found 47 genes with WRKY transcription factor binding sites in the wheat genome that have been reported to be expressed during salt stress. Provide insight into the structure and diversity of WRKY domains in wheat. Abstract: Soil salinization is an increasing global threat to economically important agricultural crops such as bread wheat ( Triticum aestivum L.). A main regulator of plants' responses to salt stress is WRKY transcription factors, a protein family that binds to DNA and alters the rate of transcription for specific genes. In this study, we identified 297 WRKY genes in the Chinese Spring wheat genome (Ensembl Plants International Wheat Genome Sequencing Consortium (IWGSC)), of which 126 were identified as putative. We classified 297 WRKY genes into three Groups: I, II (a–e) and III based on phylogenetic analysis. Principal component analysis (PCA) of WRKY proteins using physicochemical properties resulted in a very similar clustering as that observed through phylogenetic analysis. The 5` upstream regions (−2 000 bp) of 107 891 sequences from the wheat genome were used to predict WRKY transcription factor binding sites, and from this we identified 31 296 genes with putative WRKY binding motifs using the Find Individual Motif Occurrences (FIMO) tool. Among these predicted genes, 47 genes were expressed during salt stress according to a literature survey. Thus, we provide insight into the structure and diversity of WRKY domains in wheat and a foundation for future studies of DNA-binding specificity and for analysis of the transcriptional regulation of plants' response to different stressors, such as salt stress, as addressed in this study.